PEMEROLEHAN BAHASA ANAK-ANAK USIA 3 DAN 5 TAHUN DALAM DIALEK BANYUMAS DI KEJAWANG SRUWENG KEBUMEN - Monica Septiyani; Umi Hartati (CARAKA, 2018)
This study aims to (1) describe the acquisition of the language of children 3 and 5 years in Banyumas dialect, (2) to describe the differences of boys and girls in the acquisition of language-children 3 and 5 years in Banyumas dialect, and (3) describes the form of language acquisition of children 3 and 5 years old in Banyumas dialect located in Kejawang Village, Sruweng Sub-district, Kebumen District. The type of research is descriptive qualitative. Research data in the form of words, phrases, and sentences. The data source is a child of 3 and 5 years. Number of children studied there are 12 children. Every age there are 6 children, 3 women and 3 men. The method of research is the method of referring. This technique is a technically skilled libat technique. Data analysis using the method of matching. The method of presenting the results of data analysis is presented informally. The results of the study were (1) acquisition of the language of children 3 and 5 years old in Banyumas dialect, (2) differences of boys and girls 3 and 5 years in Banyumas dialect language, and (3) childrenÂ  aged 3 and 5 years in Banyumas dialect located in Kejawang Village, Sruweng Sub-district, Kebumen District.